Neuropeptide S increases motor activity and thermogenesis in the rat through sympathetic activation. (October 2017) - Ensho, Takuya; Nakahara, Keiko; Suzuki, Yoshihiro; Murakami, Noboru
Abstract: The central role of neuropeptide S (NPS), identified as the endogenous ligand for GPR154, now named neuropeptide S receptor (NPSR), has not yet been fully clarified. We examined the central role of NPS for body temperature, energy expenditure, locomotor activity and adrenal hormone secretion in rats. Intracerebroventricular (icv) injection of NPS increased body temperature in a dose-dependent manner. Energy consumption and locomotor activity were also significantly increased by icv injection of NPS. In addition, icv injection of NPS increased the peripheral blood concentration of adrenalin and corticosterone. Pretreatment with the β1- and β2-adrenergic receptor blocker timolol inhibited the NPS-induced increase of body temperature. The expression of both NPS mRNA in the brainstem and NPSR mRNA in the hypothalamus showed a nocturnal rhythm with a peak occurring during the first half of the dark period. To examine whether the endogenous NPS is involved in regulation of body temperature, NPSR antagonist SHA68 was administered one hour after darkness. SHA68 attenuated the nocturnal rise of body temperature. These results suggest that NPS contributes to the regulation of the sympathetic nervous system. Highlights: Intracerebroventricular injection of NPS increases body temperature. NPS increases oxygen consumption, locomotor activity and the plasma adrenalin level. Pretreatment with timolol inhibits this NPS-induced thermogenesis. The expression of NPS mRNA and NPSR mRNA show a diurnal variation.